Implementasi Model Project Based Learning untuk Mengembangkan Soft Skills dan Kualitas Hasil Belajar Siswa - Aep Saifullah (Jurnal Pendidikan Kewarganegaraan, 2018)
This research is a Classroom Action Research (CAR) with the aim of developing soft skills and improving the quality of student learning outcomes by implementation innovative learning is Project Based Learning (PBL). The study population was all student of class XII of the Social Sciences who took part in the study of Islamic Religion Education (PAI) consisting of IPS 1 class and IPS class 2. The research sample was students of class XII IPS 2 totaling 21 people. Data collection instruments in the form of self-assessment questionnaire, check list form and recording student behavior observation, in-depth discussion, peer evaluation and conceptual thinking ability test. Data were analyzed with quantitative descriptive techniques. The results show that through project-based learning can develop soft skills and improve the quality of student learning outcomes. Like wise students' responses to learning are positive.